Combination of ultra-rapid DNA purification (PURE) and loop-mediated isothermal amplification (LAMP) for rapid detection of Trypanosoma cruzi DNA in dried blood spots - Longhi, Silvia Andrea (2023)
Background Chagas disease or American trypanosomiasis, a neglected tropical disease, is a persistent Public Health problem in Latin America and other, non-endemic, countries. Point-of-care (POC) sensitive methods are still needed to improve and extend early diagnosis in acute infections such as congenital Chagas disease. The objective of this study was to analytically evaluate in the lab the performance of a qualitative POC molecular test (Loop-mediated isothermal amplification (LAMP), Eiken, Japan) for rapid diagnosis of congenital Chagas disease employing FTA cards or Whatman 903 filter paper as solid supports for small-scale volumes of human blood. Methodology/principal findings We used human blood samples artificially infected with cultured T. cruzi strains to assess the analytical performance of the test in comparison with liquid blood anticoagulated with heparin. The DNA extraction process was evaluated using the ultrarapid purification system PURE manufactured by Eiken Chemical Company (Tokio, Japan) over artificially infected liquid blood or different amounts of dried blood spot (DBS) 3-and 6-mm pieces of FTA and Whatman 903 paper. LAMP was performed on a AccuBlock (LabNet, USA) heater or in the Loopamp LF-160 incubator (Eiken, Japan), and visualization of results was either done at naked eye, using the LF-160 device or P51 Molecular Fluorescence Viewer (minipcr bio, USA). Best conditions tested showed a limit of detection (LoD) with 95% accuracy (19/20 replicates) of 5 and 20 parasites/mL, respectively for heparinized fluid blood or DBS sam-ples. FTA cards showed better specificity than Whatman 903 filter paper. Conclusions/significance Procedures to operate LAMP reactions from small volumes of fluid blood or DBS in FTA were standardized for LAMP detection of T. cruzi DNA. Our results encourage prospective studies in neonates born to seropositive women or oral Chagas disease outbreaks to opera-tionally evaluate the method in the field.